Effect of praziquantel on ATP uptake and metabolism of Schistosoma japonicum - Xiao Shu-hua; Wang Cui-ying; Jiao Pei-ying; Chen Guo-zhong; Yu Yue-gui; Yuan Xing-ju (Acta Pharmacologica Sinica, 2016)
When Schistosoma japonicum was exposed to culture medium containing [3H]ATP and praziquantel 0.1, 1 or 10μg/ml for 1—4 h, the [3H]ATP uptake decreased significantly in male worms, but not in females. If male schistosomes were exposed to praziquantel 1 or 10μg/ml for 1—4 h and then transferred to drug-free culture medium, the [3H]ATP uptake recovered to normal only in lower drug concentration group. The [3H]ATP uptake of male worms markedly decreased 1 h after intragastric gavage of praziquantel100 mg/kg to infected mice and recovered to normal 4 h later. However, [3H]ATP uptake of male worms was steadily inhibited 24 h after 300 mg/kg to infected mice. No effect on [3H]ATP uptake of female worms was seen. Praziquantel promoted the transformation of [3H]ATP uptaken by male worms to [3H]AMP, while the incorporation of [3H]ATP to RNA of male worms was markedly inhibited. No apparent changes were observed in female worms.